Optimistic Environmental Messaging Increases State Optimism and in vivo Pro-environmental Behavior - MacKinnon, Megan; Davis, Adam C.; Arnocky, Steven (Frontiers in Psychology, 2022)
Despite recent empirical interest, the links between optimism and pessimism with pro-environmental behavior (PEB) remain equivocal. This research is characterized by a reliance on cross-sectional data, a focus on trait-level at the neglect of state-level optimism–pessimism, and assessments of retrospective self-reported ecological behavior that are subject to response bias. To attend to these gaps, 140 North American adults (Mage = 34; SD = 11.60; 44% female) were experimentally primed with bogus optimistic or pessimistic environmental news articles, and then asked to report their levels of state optimism–pessimism, intentions to purchase green products, in vivo PEB (donating to WWF and providing contact information to join an environmental organization), and support for geoengineering technologies. Results confirmed that optimistic (versus pessimistic) environmental messaging enhanced the expression of state optimism, which then contributed to PEB and support for geoengineering. These results have important implications for the framing of environmental messaging intended to promote ecologically conscious behavior.